Supportive or inhibitive? — Analysis of dynamic interactions between the inter-organisational collaborations of vehicle powertrains. (20th January 2020) - Mirzadeh Phirouzabadi, Amir; Juniper, James; Savage, David; Blackmore, Karen
Abstract: The transition to the green mobility economy has encouraged organisations to both collaborate and compete for building the environmental innovations required in vehicle powertrains. This study aims to uncover the inhibitive and supportive impacts traded between vehicle powertrains over time. Applying the technological innovation system framework and the Lotka–Volterra model, we argue that the increased or decreased collaboration growth of one powertrain system can drive supportive and inhibitive forces towards other powertrain systems. Collaboration growth is measured through joint patents extracted from the Derwent platform for the episodes of 1985–1996, 1997–2007, and 2008–2016. Our results show that powertrain systems drive supportive, and to some extent, inhibitive forces to one another, known as positive and negative externalities. Not only the attractiveness and carrying capacity of powertrain systems change with time, but also the interaction modes between them go through temporal transitions, mostly between symbiosis, neutralism, and commensalism. We observe that the biological inter-powertrain relationships emanate from the various elements shared between them over time. We, moreover, discover that the biological relationships and their temporal transitions have shaped around a situation in which the automotive industry is moving away from the dependence on non-green innovations towards more environmentally friendly innovations. We recommend policy makers to beware of the dual role of 'creation' and 'destruction' in their policy mixes, and accordingly, devise and deploy a mix of offensive and defensive environmental strategies to each of the interaction modes as well as during the transitions between them. Highlights: Powertrains create positive/negative externalities in terms of collaboration growth. Powertrains' collaborative attractiveness and carrying capacity change with time. Interaction modes go through temporal transitions, mostly symbiosis and commensalism. Inter-powertrain relationships are moving from non-green to green innovations. Policy makers shall note the dual role of creation and destruction of policy mixes.